2020
DOI: 10.31234/osf.io/ahgfy
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Increasing Interest in Computer Science through Group Work: A Goal Congruity Approach

Abstract: Women’s underrepresentation in science, technology, engineering, and math (STEM) fields is well established; however, there is much variation in women’s among STEM fields. Women received 60% of bachelor’s degrees in biology but only 18% of computer science degrees in 2009. One explanation for this difference may be social stereotypes of the fields. Male-dominated STEM fields are stereotyped as asocial, which may lead women to think that these fields will not give them opportunities to work with and help others… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Goal opportunities in an environment might be afforded through both literal and figurative structures. For example, the placement of furniture in classrooms provides or precludes opportunities for collaboration (Cheryan et al, 2014), and STEM courses that included group work were perceived higher in communal goal affordances (Montoya et al, 2020). Prior experimental work has found that students use such information to discern their likely goal opportunities: For example, an engineering course description that included service learning led to greater expectations of communal opportunities in the course, relative to a control description (Belanger et al, 2017).…”
Section: Environmental Structures and Signalsmentioning
confidence: 99%
“…Goal opportunities in an environment might be afforded through both literal and figurative structures. For example, the placement of furniture in classrooms provides or precludes opportunities for collaboration (Cheryan et al, 2014), and STEM courses that included group work were perceived higher in communal goal affordances (Montoya et al, 2020). Prior experimental work has found that students use such information to discern their likely goal opportunities: For example, an engineering course description that included service learning led to greater expectations of communal opportunities in the course, relative to a control description (Belanger et al, 2017).…”
Section: Environmental Structures and Signalsmentioning
confidence: 99%
“…Goal opportunities in an environment might be afforded through both literal and figurative structures. For example, the placement of furniture in classrooms provides or prevents opportunities for collaboration (Cheryan et al, 2014), and STEM courses that included group work were perceived higher in communal goal affordances (Montoya et al, 2020). Prior experimental work has found that students use such information to discern their likely goal opportunities: For example, an engineering course description that included service learning led to greater expectations of communal opportunities in the course, relative to a control description (Belanger et al, 2017).…”
Section: Environmental Structures and Signalsmentioning
confidence: 99%
“…If there are order effects the following procedures will help researchers identify that they exist. The data for this example come from Montoya, Master, and Cheryan (2013). In this study, the researchers investigated if group work in computer science classes might increase women's interest in computer science by increasing their perception that computer science is a communal field.…”
Section: Example 3: Montoya Master Cheryan (2013)mentioning
confidence: 99%